An antibacterial and anti-scale silica gel material and its preparation method and application
By using antibacterial scale-proof silicone material in the shower outlet network, the problem of water effluent blockage caused by scale stains and bacterial growth is solved, and the long-term scale-proof and antibacterial effects are achieved, improving the user experience.
Patent Information
- Application Number
- CN202410979208.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-22
AI Technical Summary
The existing shower outlet nets are prone to scale stains and bacterial growth after long-term use, resulting in clogging of the outlet nozzle and reducing the user experience.
An antibacterial scale anti-scaling silicone material is used, which consists of vinyl polysiloxane, silane coupling agent, gas-phase white carbon black, cyclodextrin envelope scale-resistant anti-bacterial materials, etc. The platinum catalyst promotes graft polymerization to prepare a silicone material with long-term scale-resistant and anti-bacterial effects.
This material can effectively prevent scale and bacteria from aggregating on the surface, extend the service life of the shower outlet network, improve the stability and cleanliness of the outlet, and improve the user experience.
Smart Images

Figure GDA0005266504600000041 
Figure GDA0005266504600000091 
Figure GDA0005266504600000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silica gel materials, and in particular to an antibacterial and anti-scale silica gel material and a preparation method and application thereof. Background Art
[0002] At present, most showerhead water outlet nets are produced by silicone injection molding. Although silicone materials have certain hydrophobic properties, the products prepared after mold molding have general hydrophobic properties and are easy to scale. This is mainly caused by the surface structure of the mold, such as unpolished and fine lines, which reduce the smoothness of the surface of the silicone product, making it easy for bacteria and scale to accumulate on it. Therefore, after long-term use, the showerhead water outlet net is prone to residual scale stains and bacteria on the water surface, especially on the nozzle surface, causing the water flow of the water outlet nozzle to change or even block, thereby reducing the consumer's experience. Nowadays, people have higher and higher requirements for the experience of showers, especially for the water outlet conditions of showers (water shape, strength, whether it is blocked). On the one hand, they hope that the showerhead is antibacterial and healthy, and on the other hand, they hope that the water shape of the showerhead is stable and the strength is consistent, and there is no blockage due to scale accumulation. In response to the problem of showerhead water blockage, the current main measure is to scrub the showerhead water outlet net vigorously from time to time to remove the scale and use it again, but this method is more laborious and greatly reduces the consumer's experience. Summary of the invention
[0003] The present invention aims to solve at least one of the above-mentioned technical problems in the related art to a certain extent. To this end, the present invention proposes an antibacterial and anti-scale silica gel material and its preparation method and application, which can achieve a long-lasting antibacterial function on the one hand and improve the anti-scale function of the shower head on the other hand to meet the use needs of consumers.
[0004] To achieve the above object, the technical solution of the present invention is as follows:
[0005] The present invention provides a silica gel material, and the raw materials for preparing the silica gel material include component A and component B, wherein the component A includes: vinyl polysiloxane, a first silane coupling agent, fumed silica and a platinum catalyst; the component B includes: vinyl polysiloxane, a first silane coupling agent, fumed silica, hydrogen-containing polysiloxane, an inhibitor and a composite antiscaling and antibacterial material; the composite antiscaling and antibacterial material is prepared by encapsulating an antiscaling agent and an antibacterial agent with cyclodextrin.
[0006] Cyclodextrin (abbreviated as CD) is a general term for a series of cyclic oligosaccharides generated by amylose under the action of cyclodextrin glucosyltransferase produced by Bacillus, usually containing 6-12 D-pyranose units. According to the results of X-ray crystal diffraction, infrared spectroscopy and nuclear magnetic resonance spectroscopy analysis, it is determined that each D(+)-pyranose constituting the cyclodextrin molecule is in a chair conformation. Each glucose unit is linked to a ring by a 1,4-glycosidic bond. Since the glycosidic bonds connecting the glucose units cannot rotate freely, cyclodextrin is not a cylindrical molecule but a slightly conical ring.
[0007] The shape of the cyclodextrin molecule is a slightly conical hollow structure with "hydrophobic inside and hydrophilic outside". Two different types of hydroxyl groups are bonded along the upper and lower edges of the cyclodextrin ring. Secondary hydroxyl groups are bonded to the C-2 and C-3 positions of the glucose ring, which are located on the upper larger edge of the CD ring; primary hydroxyl groups are bonded to the C-6 position of the glucose ring through the hydroxyl group, which are located on the lower smaller edge of the CD ring. The upper and lower edges of the CD ring are very hydrophilic due to the presence of these hydroxyl groups. In contrast, the inner surface of the CD ring is embedded with relatively non-polar methylene groups and oxygen groups, which make the inner surface of the CD ring more organic-philic (i.e., hydrophobic). The CD ring can be dissolved in many polar solvents including water, and can be modified by the derivatization of hydroxyl groups to obtain the desired chemical and physical properties. It is this special structure that allows cyclodextrin to act as a "host" to contain different "guest" compounds.
[0008] In some embodiments of the present invention, the scale inhibitor is sodium polyaspartate, and the antibacterial agent is oligohydroxybutyrate. Sodium polyaspartate is in powder form, with a particle size D50 of 0.5-5um and an effective content of more than 98%. Sodium polyaspartate and oligohydroxybutyrate contain polar groups and non-polar groups, respectively, which can be firmly "chelated" with the polar groups and non-polar groups of cyclodextrin, making sodium polyaspartate and oligohydroxybutyrate more easily encapsulated by cyclodextrin. Further,
[0009] Sodium polyaspartate (PASP for short) is a water-soluble polymer and a new type of green water treatment agent. It is phosphorus-free, non-toxic, pollution-free and completely biodegradable. It has a strong chelating ability for ions and has the dual effects of corrosion and scale inhibition. It has a good scale inhibition effect on scale-forming salts such as calcium carbonate, calcium sulfate, barium sulfate, and calcium phosphate. The scale inhibition rate for calcium carbonate can reach 100%. PASP can replace phosphorus-containing water treatment agents to avoid eutrophication of water bodies and secondary pollution of discharge.
[0010] Oligohydroxybutyrate (OPHB) is an environmentally friendly and safe bio-based antimicrobial agent. Its main raw material is the bio-based polymer material PHBV (poly 3-hydroxybutyrate valerate) prepared from non-GMO corn. OPHB is a non-ionic bio-based environmentally friendly organic antimicrobial agent that can destroy the biofilm and cell wall of bacteria, causing the leakage of intracellular substances of bacteria and killing bacteria. OPHB can destroy the lipid protein that encapsulates RNA of viruses, killing the viruses. At the same time, the antimicrobial agent can be completely biodegraded under composting conditions and is friendly to environmental protection. Therefore, OPHB antimicrobial agent has the characteristics of environmental protection and safety.
[0011] The principle of the present invention is to use the slightly conical cavity structure of cyclodextrin molecules with "hydrophobic inside and hydrophilic outside" to first encapsulate the scale inhibitor and antibacterial agent under certain conditions, and then graft polymerize with vinyl polysiloxane (MVMQ) under the action of platinum catalyst to prepare environmentally friendly antibacterial and anti-scale silica gel materials. The following is a reaction principle diagram taking β-cyclodextrin, PASP, and OPHB as examples:
[0012]
[0013] In some embodiments of the present invention, the component A is calculated by the following mass parts: 30-80 parts of vinyl polysiloxane, 3-8 parts of the first silane coupling agent, 30-50 parts of fumed silica and 0.2-1 parts of platinum catalyst; the component B is calculated by the following mass parts: 30-80 parts of vinyl polysiloxane, 3-8 parts of the first silane coupling agent, 30-50 parts of fumed silica, 2-10 parts of hydrogen-containing polysiloxane, 0.1-0.6 parts of inhibitor and 1-10 parts of composite antiscaling and antibacterial material. Further, the inhibitor is 0.3-0.5 parts.
[0014] In some embodiments of the present invention, the mass ratio of the cyclodextrin, the scale inhibitor and the antibacterial agent is 6:(2-4):(0.5-2).
[0015] In some embodiments of the present invention, the composite anti-scaling and antibacterial material is prepared by the following method: solid cyclodextrin is prepared into a cyclodextrin solution, a scale inhibitor and an antibacterial agent are added to the cyclodextrin solution, the obtained mixed solution is stirred at a temperature of 40-70°C, and after stirring, the mixture is allowed to stand and dried to obtain the composite anti-scaling and antibacterial material. Further, the mass concentration of the cyclodextrin solution is 10%-40%. Further, the obtained mixed solution is stirred at a speed of 2000-2500rpm at a temperature of 40-70°C, and the stirring time is 2-4h.
[0016] In some embodiments of the present invention, the first silane coupling agent is at least one of dimethyldiethoxysilane, dimethyldimethoxysilane, dimethylcyclosiloxane or hexamethyldisilazane.
[0017] In some embodiments of the present invention, the vinyl mass percentage of the vinyl polysiloxane is 0.2-1.0%, and the viscosity at 25° C. is 5000-10000 mPa.s.
[0018] In some embodiments of the present invention, the mass percentage of hydrogen in the hydrogen-containing polysiloxane is 0.05-1%.
[0019] In some embodiments of the present invention, the platinum catalyst is at least one of a tetramethyldivinyldisiloxane chloroplatinic acid complex, a platinum-alkyne complex or an isopropanol solution of chloroplatinic acid; and the mass content of platinum in the platinum catalyst is 1000-1500 ppm.
[0020] In some embodiments of the present invention, the inhibitor is at least one of polyvinyl polysiloxane, acetylene alcohol compounds, amide compounds or cyano compounds. Further, the acetylene alcohol compound is at least one of 2-propyn-1-ol, methyl butynol, ethynyl cyclohexanol, phenyl butynol or 3,5-dimethyl-1-hexyn-3-ol.
[0021] In some embodiments of the present invention, the fumed silica is a surface-treated fumed silica, and the surface treatment process is as follows: the fumed silica is placed in a vacuum and dried, and the dried fumed silica is fed into a fluidized bed reactor, and the second silane coupling agent is vaporized and introduced into the fluidized bed reactor with an inert gas as a carrier for a first reaction, and after the first reaction is completed, microcrystalline wax is fed into the fluidized bed reactor, and a second reaction is carried out at 170-230°C to obtain a surface-treated fumed silica. The effective content of the microcrystalline wax is greater than 98%. Further, the fumed silica is dried in a vacuum for 3-5 hours. Further, the flow rate of the fumed silica fed into the fluidized bed reactor is 30-50 g / min, the flow rate of the second silane coupling agent into the fluidized bed reactor is 5-8 g / min, the vaporization temperature of the second silane coupling agent is 150-190°C, and the time of the first reaction is 1-3 hours. Furthermore, the flow rate of the microcrystalline wax fed to the fluidized bed reactor is 3-6 g / min, and the second reaction time is 2-4 h. Furthermore, the SiO2 content of the fumed silica is greater than 99%, the D50 is 3-50 nm, and the specific surface area is 120-300 m 2 / g. Further preferably, the D50 of the fumed silica is 8-17nm.
[0022] In some embodiments of the present invention, the second silane coupling agent is at least one of alkoxysilane, vinylalkoxysilane or chlorosilane. Further, the vinylalkoxysilane is at least one of vinyltrimethoxysilane or vinyldiethoxysilane; the alkoxysilane is at least one of hexamethylcyclotrisiloxane and octamethylcyclotetrasiloxane; the chlorosilane is at least one of dimethyldichlorosilane or trimethylchlorosilane.
[0023] In some embodiments of the present invention, the mass ratio of the fumed silica, the second silane coupling agent and the microcrystalline wax is 6:(1-2):(0.5-1).
[0024] In some embodiments of the present invention, the cyclodextrin is at least one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin. The α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, i.e., the number of D-pyranose units, are 6, 7 and 8 respectively, in powder form, with a particle size D50 of 0.3-5um and an effective content greater than 99%.
[0025] In some embodiments of the present invention, the degree of polymerization of the oligohydroxybutyrate is 1-15. Preferably, the degree of polymerization of the oligohydroxybutyrate is 4-8.
[0026] The present invention also provides a method for preparing the silica gel material, comprising the following steps:
[0027] Preparation of component A: mixing and stirring the first silane coupling agent, fumed silica and 30%-70% of the formula amount of vinyl polysiloxane, vacuum degassing, and then adding the remaining formula amount of vinyl polysiloxane and platinum catalyst and stirring to obtain component A;
[0028] Preparation of component B: mixing and stirring the first silane coupling agent, fumed silica and 30%-70% of the formula amount of vinyl polysiloxane, vacuum degassing, and then adding the remaining formula amount of vinyl polysiloxane, hydrogen-containing polysiloxane, inhibitor and composite antiscaling and antibacterial material and stirring to obtain component B;
[0029] The silica gel material is obtained by mixing component A and component B and then performing injection molding.
[0030] In some embodiments of the present invention, the mixing and stirring time is 1-4 hours.
[0031] In some embodiments of the present invention, the vacuum degassing is carried out at 110-170° C. and stirring for 1-4 hours under vacuum conditions.
[0032] In some embodiments of the present invention, the process conditions of the injection molding are: injection temperature of 90-160°C, injection time of 2-8 min, injection pressure of 40-120 kg / cm2 .
[0033] The present invention also proposes the use of the silica gel material in a shower water outlet net or a shower water outlet nozzle.
[0034] According to a preferred embodiment of the present invention, there are at least the following beneficial effects:
[0035] The present invention utilizes cyclodextrin to encapsulate a scale inhibitor and an antibacterial agent under certain conditions to obtain a composite scale inhibitor and antibacterial material. Since cyclodextrin is a typical conical hollow structure, cyclodextrin can serve as a "host" to contain compounds of different "guests". After encapsulation, the scale inhibitor and the antibacterial agent are firmly encapsulated in the cavity of the cyclodextrin. Then, under the catalytic action of platinum, the cyclodextrin undergoes an addition grafting reaction with the unsaturated carbon-carbon double bond C=C of vinyl polysiloxane through the secondary hydroxyl groups at the C-2 and C-3 positions of the ring. At the same time, the vinyl polysiloxane also undergoes a homopolymerization self-polymerization reaction, and finally a silica gel material bonded with an antibacterial and scale-proof slow-release body is obtained. Since cyclodextrin contains glucose units, it is highly hydrophilic and has poor compatibility with hydrophobic two-component liquid silicone. Therefore, the more active glucose units are used to carry out grafting reaction with vinyl polysiloxane to enhance the compatibility of the composite anti-scaling and antibacterial material with the two-component liquid silicone system, thereby making the prepared antibacterial and anti-scale silicone material more stable and effective, ensuring that the scale inhibitors and antibacterial agents can be slowly released outward under the use scenario, thereby achieving long-term scale inhibition and antibacterial effects.
[0036] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0038] Table 1 Antibacterial and anti-scale showerhead silicone water outlet sheet formula
[0039]
[0040] Table 1 related instructions:
[0041] (1) The vinyl mass percentage of the vinyl polysiloxane is 0.6%, and the viscosity is 8000 mPa.s at 25°C.
[0042] (2) The degree of polymerization of OPHB is 4.
[0043] (3) Preparation of surface treated fumed silica: The preparation of antibacterial and anti-scale silicone showerhead water outlet sheet includes the following steps: ordinary fumed silica is placed in a vacuum at 130°C and dried for 4 hours, and then the dried fumed silica is fed into a fluidized bed reactor through a rotary feeding valve at a rate of 30 g / min. At the same time, the silane coupling agent vinyl trimethoxysilane is vaporized at 170°C at a rate of 5 g / min through a flow meter and then introduced into the reactor from the bottom of the fluidized bed reactor with N2 as a carrier, and reacted for 2 hours. Then, microcrystalline wax is fed into the fluidized bed reactor at a rate of 3 g / min through a flow meter, and the reaction temperature is controlled at 190°C. The reaction is carried out for 2 hours and the surface treated fumed silica is obtained.
[0044] (4) Preparation of composite antiscaling and antibacterial materials: Powdered β-cyclodextrin is used to prepare a β-cyclodextrin solution with a mass concentration of 30%, which is placed in a reactor and allowed to stand. Then, the scale inhibitor sodium polyaspartate PASP and the bio-based antibacterial agent oligohydroxybutyrate (OPHB) are added at room temperature with stirring. The mass ratio of β-cyclodextrin, scale inhibitor and antibacterial agent is 6:3:1. The mixture is stirred continuously at a speed of 2000 rpm in a constant temperature water bath at 60°C for 3 hours. After stirring evenly, the mixture is allowed to stand for 24 hours and dried to obtain a composite antiscaling and antibacterial material.
[0045] The preparation of antibacterial and anti-scale showerhead silicone water outlet sheet includes the following steps:
[0046] (1) Preparation of liquid silicone material
[0047] Preparation of component A:
[0048] First, add 60% of the formula amount of vinyl polysiloxane, silane coupling agent and surface-treated fumed silica into a kneader, stir at room temperature for 2 hours, heat to 160°C, stir under vacuum for 2 hours, then stop the vacuum, continue to add the remaining formula amount of vinyl polysiloxane for dilution, then add platinum catalyst, stir evenly, and obtain component A.
[0049] Preparation of component B:
[0050] First, add 60% of the formula amount of vinyl polysiloxane, silane coupling agent and fumed silica into a kneader, stir at room temperature for 2 hours, heat to 160°C, stir under vacuum for 2 hours, then stop the vacuum, continue to add the remaining formula amount of vinyl polysiloxane for dilution, and then add hydrogen-containing polysiloxane, inhibitor and composite antiscaling and antibacterial material and stir evenly to obtain component B.
[0051] (2) Molding of showerhead silicone water outlet sheet: The prepared component A and component B are mixed by a feeder at a mass ratio of 1:1 through a mixer and then pumped into an injection molding machine. The showerhead silicone water outlet sheet product is processed and manufactured on the injection molding machine using the prepared mold. The molding process conditions are: injection temperature of 150°C, injection time of 5 minutes, and injection pressure of 80kg / cm 2 , and obtain the antibacterial and anti-scale silicone water outlet sheet for shower head.
[0052] The corresponding samples of each embodiment and comparative example were prepared according to the formulation in Table 1 and the above preparation steps.
[0053] Test example
[0054] In this test example, the antibacterial and anti-scale properties of the antibacterial and anti-scale silicone water outlet sheets prepared in the examples and comparative examples were tested according to the following test methods. The results are shown in Table 2.
[0055] (1) Antibacterial test
[0056] Antibacterial performance test: tested according to the method of GB / T 31402-2015.
[0057] Antibacterial durability test: After placing each test sample in a 70°C water environment for 30 days, the antibacterial performance of the sample was tested according to the above-mentioned antibacterial performance test method.
[0058] (2) Shore A hardness test
[0059] The test is carried out in accordance with the provisions of GB / T531-2008 "Test method for Shore A hardness of vulcanized rubber". The Shore A hardness is used to evaluate the softness of the silicone water outlet of the shower head.
[0060] (3) Tensile performance test
[0061] The test was carried out in accordance with the provisions of GB / T 1040.1-2018 "Determination of tensile properties of plastics". The tensile strength was tested using a microcomputer-controlled electronic universal testing machine to evaluate the effect of the formulation system on the tensile properties.
[0062] (4) Anti-scale performance test
[0063] The test is carried out in accordance with the provisions of GB / T 16632-2008 "Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method". The sample is installed, a water supply pressure of 0.55MPa is provided, and the concentration of calcium carbonate in the water is 1000mg / mL hardness water source. The water is discharged for 30 minutes and then left to stand for 12 hours. After 60 cycles, the scale inhibition rate is tested. The higher the scale inhibition rate, the better the anti-scale effect of the material.
[0064] Calculation formula for scale inhibition rate: scale inhibition rate = (1-(AB) / A)*100%
[0065] Among them, A represents the concentration of calcium carbonate salt in untreated water sample, the unit is mg / mL; B represents the concentration of calcium carbonate salt in treated water sample, the unit is mg / mL.
[0066] (5) Friction coefficient test
[0067] The test is carried out in accordance with the provisions of GB / T 10006-2021 "Determination of friction coefficient of plastic films and sheets". The size of the static friction coefficient and the dynamic friction coefficient are used to evaluate the smoothness of the material surface. The smaller the friction coefficient, the smoother the material surface is, and the less likely bacteria and scale are to accumulate on it.
[0068] Table 2 Performance test results
[0069]
[0070] From Examples 1-5, as the content of the composite anti-scaling and antibacterial material in the formula system increases, the initial antibacterial performance of the product and the high-temperature water boiling lasting antibacterial performance gradually improve, the scale inhibition rate also gradually increases, and the static friction coefficient and the dynamic friction coefficient gradually decrease; when the content of the composite anti-scaling and antibacterial material in component B is increased to 8%, the above properties are best in combination, among which the initial antibacterial rate and the high-temperature water boiling lasting antibacterial rate for Escherichia coli and Staphylococcus aureus are greater than 99.9%, the Shore A hardness is 43A, the tensile strength is 6.1MPa, the scale inhibition rate measured by the calcium carbonate deposition method is increased to 95.32%, and the static friction coefficient and the dynamic friction coefficient are reduced to 0.42 and 0.25 respectively. The decrease in the friction coefficient is due to the fact that the glucose unit structure of cyclodextrin can react with water to form a film on the surface of the material that is conducive to the hydration and lubrication effect, thereby reducing the overall resistance experienced when the friction surface is rubbed.
[0071] From Example 1 and Comparative Example 1, the scale inhibitor sodium polyaspartate PASP and the antibacterial agent OPHB are encapsulated by cyclodextrin and then grafted with vinyl polysiloxane, and the above properties are in the best state. This is because cyclodextrin is a slightly conical cavity structure with "hydrophobic inside and hydrophilic outside", which can be used as a "host" to encapsulate different "guest" compounds; after encapsulation, β-cyclodextrin is then subjected to addition grafting reaction with the unsaturated carbon-carbon double bond C=C of vinyl polysiloxane through the secondary hydroxyl groups at the C-2 and C-3 positions of the glucose ring. After encapsulation and grafting, the scale inhibitor sodium polyaspartate PASP and the antibacterial agent OPHB can exert scale inhibition and antibacterial effects for a long time, which is significantly different from the effect of not being encapsulated and free outside the polymer system. Before encapsulation, PASP and OPHB contain many polar groups such as -NH- and -OH, which are very hydrophilic and can easily migrate to the surface in an aqueous environment and be lost instantly, resulting in functional failure. After encapsulation, they are firmly trapped in the spatial structure of cyclodextrin, and cyclodextrin is bonded to the silica gel system due to grafting with vinyl polysiloxane, which can better exert its sustained-release effect.
[0072] From Example 1 and Comparative Examples 2-4, in the process of the reaction between cyclodextrin and vinyl polysiloxane, the secondary hydroxyl groups at the C-2 and C-3 positions of the glucose ring and the Si-H on the hydrogen-containing polysiloxane of the same component will simultaneously undergo copolymerization and addition grafting reaction with the unsaturated carbon-carbon double bond C=C, and at the same time, the vinyl polysiloxane will also undergo homopolymerization and self-polymerization, so that "competitive polymerization" between copolymerization and self-polymerization will occur, which can be controlled by controlling the content of the inhibitor 2-propynyl-1-ol. Too little (such as Comparative Examples 2 and 3) or too much (such as Comparative Example 4) of the inhibitor 2-propynyl-1-ol will have side effects on the comprehensive performance of the product. In this formulation system, the content of 2-propynyl-1-ol in component B is 0.5 parts, which is more suitable.
[0073] From Example 1 and Comparative Example 5, the surface treatment of fumed silica will also affect the performance of the product. After surface treatment with silane coupling agent and microcrystalline wax, the static friction coefficient and dynamic friction coefficient of the material decreased significantly, which also reduced the probability of bacteria and scale depositing on the surface of the material to a certain extent. This is because the organic group of the silane coupling agent is connected to the surface of fumed silica by the reaction of silane coupling agent with the silanol of fumed silica, which reduces the number of silanols on the surface of fumed silica, making it hydrophilic to hydrophobic, thereby improving its compatibility with organic matter, and then increasing its dispersibility in polymers, which can be well bonded to fill the microporous gaps on the surface of silica gel. At the same time, due to the introduction of microcrystalline wax, the surface finish of fumed silica is changed, becoming more lubricated, making it difficult for bacteria and scale to deposit on the surface of the material, and improving the antibacterial and anti-scale properties of the product. In addition, the surface-treated fumed silica is more tightly and firmly combined with the two-component liquid silicone resin, reflecting the effect of filling enhancement, so the hardness and tensile strength are also improved.
[0074] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A silica gel material, characterized in that: The preparation raw materials include component A and component B, wherein the component A includes: vinyl polysiloxane, a first silane coupling agent, fumed silica and a platinum catalyst; the component B includes: vinyl polysiloxane, a first silane coupling agent, fumed silica, hydrogen-containing polysiloxane, an inhibitor and a composite anti-scaling and antibacterial material; the composite anti-scaling and anti-bacterial material is prepared by encapsulating a cyclodextrin anti-scaling agent and an antibacterial agent; the anti-scaling agent is sodium polyaspartate; the antibacterial agent is oligohydroxybutyrate; the component A is calculated in the following mass parts: 30-80 parts of vinyl polysiloxane, 3-8 parts of the first silane coupling agent, 30-50 parts of fumed silica and 0.2-1 parts of the platinum catalyst; The B component is calculated in the following parts by mass: 30-80 parts of vinyl polysiloxane, 3-8 parts of the first silane coupling agent, 30-50 parts of fumed silica, 2-10 parts of hydrogen-containing polysiloxane, 0.1-0.6 parts of inhibitor and 1-10 parts of composite anti-scaling and antibacterial material; the mass ratio of the cyclodextrin, the anti-scaling agent and the anti-bacterial agent is 6: (2-4): (0.5-2); the composite anti-scaling and anti-bacterial material is prepared by the following method: solid cyclodextrin is prepared into a cyclodextrin solution, the anti-scaling agent and the anti-bacterial agent are added to the cyclodextrin solution, the obtained mixed solution is stirred at a temperature of 40-70°C, the stirring is completed, and the mixed solution is allowed to stand, and the composite anti-scaling and anti-bacterial material is obtained by drying.
2. The silica gel material according to claim 1, characterized in that: The fumed silica is a surface-treated fumed silica, and the surface treatment process is as follows: the fumed silica is placed in a vacuum and dried, and the dried fumed silica is fed into a fluidized bed reactor, and at the same time, a second silane coupling agent is vaporized and introduced into the fluidized bed reactor with an inert gas as a carrier to perform a first reaction, and after the first reaction is completed, microcrystalline wax is fed into the fluidized bed reactor, and a second reaction is performed at 170-230° C. to obtain the surface-treated fumed silica.
3. The silica gel material according to claim 2, characterized in that: The mass ratio of the fumed silica, the second silane coupling agent and the microcrystalline wax is 6:(1-2):(0.5-1).
4. The silica gel material according to claim 1, characterized in that: The cyclodextrin is at least one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.
5. The method for preparing the silica gel material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Preparation of component A: mixing and stirring the first silane coupling agent, fumed silica and 30%-70% of the formula amount of vinyl polysiloxane, vacuum degassing, and then adding the remaining formula amount of vinyl polysiloxane and platinum catalyst and stirring to obtain component A; Preparation of component B: mixing and stirring the first silane coupling agent, fumed silica and 30%-70% of the formula amount of vinyl polysiloxane, vacuum degassing, and then adding the remaining formula amount of vinyl polysiloxane, hydrogen-containing polysiloxane, inhibitor and composite antiscaling and antibacterial material and stirring to obtain component B; The silica gel material is obtained by mixing component A and component B and then performing injection molding.
6. Use of the silica gel material according to any one of claims 1 to 4 in a showerhead water outlet net or a showerhead water outlet nozzle.
Citation Information
Patent Citations
Application of beta-cyclodextrin polymer and gray water scale inhibition and dispersion agent compound
CN117361762A
Bio-based antibacterial silica gel material as well as preparation method and application thereof
CN117701005A